2020
DOI: 10.3390/ijms21113913
|View full text |Cite
|
Sign up to set email alerts
|

Acetylcholinesterase Inhibition of Diversely Functionalized Quinolinones for Alzheimer’s Disease Therapy

Abstract: In this communication, we report the synthesis and cholinesterase (ChE)/monoamine oxidase (MAO) inhibition of 19 quinolinones (QN1-19) and 13 dihydroquinolinones (DQN1-13) designed as potential multitarget small molecules (MSM) for Alzheimer’s disease therapy. Contrary to our expectations, none of them showed significant human recombinant MAO inhibition, but compounds QN8, QN9, and DQN7 displayed promising human recombinant acetylcholinesterase (hrAChE) and butyrylcholinesterase (hrBuChE) inhibition. In partic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…Electronic supplementary information (ESI): General experimental procedures, m.p., spectral data ( 1 H-, 13 C-NMR and IR) and elemental analyses of the synthesized compounds; Copies of…”
Section: Supporting Information Summarymentioning
confidence: 99%
See 2 more Smart Citations
“…Electronic supplementary information (ESI): General experimental procedures, m.p., spectral data ( 1 H-, 13 C-NMR and IR) and elemental analyses of the synthesized compounds; Copies of…”
Section: Supporting Information Summarymentioning
confidence: 99%
“… [4,10] These analogues were constructed by substituting the pharmacophoric indanone unit for a chromene unit [11,12] . Due to the fact that piperazine is a bio‐isosteric unit of piperidine, several studies have looked into the use of piperazine in the synthesis of potential AChE inhibitors [13,14] . According to a recent study by Mozaffarnia et al., [15] donepezil analogues′ inhibitory activity was enhanced when the piperidine part was switched out for a piperazine unit.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“… [4,13] These analogs were mainly designed by replacing the anti‐AChE pharmacophore, indanone unit, with a chromene unit [14,15] . Piperazine is a bio‐isosteric unit of piperidine; therefore, several reports investigated the utility of piperazine in the synthesis of promising AChE inhibitors [16,17] . Mozaffarnia et al.…”
Section: Introductionmentioning
confidence: 99%
“…[14,15] Piperazine is a bioisosteric unit of piperidine; therefore, several reports investigated the utility of piperazine in the synthesis of promising AChE inhibitors. [16,17] Mozaffarnia et al recently reported that replacing the piperidine part with a piperazine unit improved the inhibitory activity of donepezil-analogs. [18] Furthermore, the promising AChE inhibitory activity of pyrazole-based scaffolds has been investigated in numerous reports.…”
Section: Introductionmentioning
confidence: 99%